MODEL OF ESTIMATION OF PROFESSIONAL COMPETENCE AND LEVEL OF QUALIFICATION OF TEACHERS-PSYCHOLOGISTS BASED ON PROFESSIONAL STANDARD "TEACHER-PSYCHOLOGIST (PSYCHOLOGIST IN SPHERE OF EDUCATION)" - E. N. Volkova (Вестник Мининского университета, 2017)
Introduction. The article tackles the main components of the model of assessment of professional competences and skill level of psychologists in education, taking into consideration professional standard requirements. It is shown that the activity of the psychologist in an education system (educational psychologist) is currently undergoing essential transformations. It is determined by need to increase its quality in the educational environment of a new type. The considerable demand for psychological services in an education system is caused, first of all, by increasing attention to the development of intellectual and personal potential of younger generation reflected in modern educational standards and the Education law. According to it, the requirements to qualification and professional competences of a psychologist are increasing that allows carrying out labor functions effectively according to the professional standards. Development of uniform system of a professional certification of educational psychologists acts as an important stage of implementation of the professional standard of the educational psychologist.Methods and materials. Research methods: theoretical analysis, generalization, systematization, classification. Research materials: The standard and legal documents regulating work of the psychologist, the professional Educational psychologist standard adopted by the Order of the Ministry of Labour and Social Protection of the Russian Federation of July 24, 2015 of N 514 N.Results. The model of certification of educational psychologists constructed on the basis of the professional standard "The Educational Psychologist (the Psychologist in Education)", including the purposes, tasks, the principles of carrying out certification, the system of criteria and indicators of assessment of professional competences is presented in the article. The criteria system includes the invariant (obligatory) and variable criteria considering specifics of activity of the expert in the educational organization and distinctive features of the contingent of students. The content of criteria reflects the main types of psychoprophylaxis in the educational organization (psychological diagnostics, psychological consultation, psychological correction, and psychological education) and also ethical and standard legal support of activity of the educational psychologist. Compliance to the criteria is estimated concretized indicators are used to assess the compliance with the criteria allowing to provide quantitative and qualitative assessment of the professional competences providing proper performance by the educational psychologist of his duties.Discussion and conclusions. The developed criteria system of certification of educational psychologists meets the requirements of the professional standard and corresponds to target reference points of preventive model of psychological service in education. At the same time, further development and deployment of system of certification of educational psychologists assumes the solution of the prospective tasks connected with specification of functional structure of activity of the educational psychologist, improvement of mechanisms of certification, definition of the directions of development of psychological service of education in general.